A construção de um lugar para a psicologia em hospitais de Sergipe - Vieira, Célia Maria Alcântara Machado (2006)
The aim of this study is to understand the means by which Psychologists have been inserted into hospitals in the state of Sergipe. I intended to contribute to the historiography of the psychology in Brazil, putting into evidence the data about the Northeast region of the country, which is less mentioned in the specific bibliography. It has been traced a historical background of the institutions which cared for the ill throughout the time, in their historical phases, the population which they cared for, their objectives, the characteristics of the care in each time, ranging from the temples of the Ancient Age, to the contemporaneous hospital, in the modernity. I have still underlined the relationships established between psychology and medicine in Brazil, since colonial time until nowadays and beyond that, a brief historical presentation of psychology insertion in hospitals in Brazil, from a bibliographic review. The research itself consisted of background informations about the State of Sergipe, the presence of Psychology courses and college, the hospitals that have psychologists working in them, and a bunch of interviews to psychologists who have worked or are still working for such institutions, in a way to get to know their contact with this specific field since their time of graduation, how they got inserted into the hospital, what s their task, what they think and what they feel about these very same informations. Data of 36 psychologists, working in 12 different hospitals in the city of Aracaju, were obtained from National Health Entities Registry (Cadastro Nacional de Estabelecimentos de Saúde - CNES) of Brazilian Health Ministry, out of which 28 professionals were interviewed. A chronologic retrospective about the work of psychologists in the hospitals in Sergipe was then drawn, and understandings about their performance, their perspectives, deceptions, threats, possibilities, and solutions. Although the points raised were mostly about the psychologists in hospitals in Sergipe, the arguments can be extrapolated to hospitals in many different parts of the country, notwithstanding the level of attention (primary, secondary or tertiary) to which they are committed, because of the likeliness of the aspects highlighted here and those presented by many authors in Brazil